2017
DOI: 10.1590/0103-6440201601409
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Biocompatibility of the Psidium cattleianum Extracts for Endodontic Purposes

Abstract: Psidium cattleianum (PC) has been displaying inhibitory effect against a variety of microorganisms, but this effect has not yet been tested against endodontic pathogens. The aim of this study was to evaluate the antimicrobial activity and biocompatibility of the aqueous (PCAE) and hydroethanolic (PCHE) extracts from Psidium cattleianum (PC) leaves. Minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC) were determined using the microdilution broth method in order to analyze the antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(11 reference statements)
1
5
0
1
Order By: Relevance
“…Despite its use in endodontics, both E. faecalis and C. albicans are very resistant to the action of calcium hydroxide [40][41][42], and its mixing with another medicament could improve significantly the antimicrobial effect [43,44], since most of the substances used as a vehicle for calcium hydroxide do not have significant antimicrobial activity. A research conducted by Dezan-Junior [45] showed that the association of calcium hydroxide and Psidium cattleianum eliminated E. faecalis in 24 h, corroborating a recent study with hydroethanolic association [46], suggesting that only the presence of the leaf extract produced bactericidal effect. The microbial inoculation sequence used in this study was performed according to the proliferation ability of the E.faecalis and C.albicans.…”
Section: Discussionsupporting
confidence: 80%
“…Despite its use in endodontics, both E. faecalis and C. albicans are very resistant to the action of calcium hydroxide [40][41][42], and its mixing with another medicament could improve significantly the antimicrobial effect [43,44], since most of the substances used as a vehicle for calcium hydroxide do not have significant antimicrobial activity. A research conducted by Dezan-Junior [45] showed that the association of calcium hydroxide and Psidium cattleianum eliminated E. faecalis in 24 h, corroborating a recent study with hydroethanolic association [46], suggesting that only the presence of the leaf extract produced bactericidal effect. The microbial inoculation sequence used in this study was performed according to the proliferation ability of the E.faecalis and C.albicans.…”
Section: Discussionsupporting
confidence: 80%
“…Traditionally, the extraction of polyphenols from PC leaves was performed using conventional methods (stirring, pressing, maceration, and hydrodistillation) with or without thermal treatments [ 13 , 14 ]. Different authors used decoction (100 g of dried leaves/600 mL deionized water at 100 °C for 5 min) [ 15 , 16 , 17 ], Soxhlet or heat reflux extraction (2 g of dried leaves/100 mL of hexane at 90 °C for 90 min) [ 18 ], hydro-distillation (for 2 to 5 h in a modified Clevenger apparatus) [ 19 , 20 ], stirring at room temperature (1.2 kg of dried leaves/12 L of 80% methanol for 3 days) [ 21 , 22 ], hand-shaking (20 g of dried leaves/250 mL of 80% ethanol, shaking vigorously 5 times a day for 12 days) [ 23 ], and maceration at room temperature with methanol (1.2 kg of dried leaves/12 L of 80% methanol for 14 days) [ 24 ] or ethanol (0.5 kg of dried leaves/500 mL for 5 days) [ 11 ] to extract bioactive compounds from PC leaves. However, these methods required high amounts of solvents and samples, and long extraction times that may affect the stability (oxidation, ionization, and hydrolysis), yield, and bioactivity of these phytochemicals [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm assays were performed with the extracts/fractions that presented 100% growth inhibition in the MBC/MFC tests, except for C. albicans, as described by Massunari et al (2017). Briefly, 96-well microplates, U-shaped bottom, were pretreated with 200µl of artificial saliva per well for 4 h at 37°C in 5% CO 2 (coating phase).…”
Section: Methodsmentioning
confidence: 99%